5x-1x=15-x

Simple and best practice solution for 5x-1x=15-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-1x=15-x equation:


Simplifying
5x + -1x = 15 + -1x

Combine like terms: 5x + -1x = 4x
4x = 15 + -1x

Solving
4x = 15 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
4x + x = 15 + -1x + x

Combine like terms: 4x + x = 5x
5x = 15 + -1x + x

Combine like terms: -1x + x = 0
5x = 15 + 0
5x = 15

Divide each side by '5'.
x = 3

Simplifying
x = 3

See similar equations:

| 7(x-6)+28=-21 | | 4x+(4-4x)=4 | | x/21=-3 | | -144=-6k | | 6(6-5)+36-7= | | -1x+8=-7x+2 | | -1x+8=7x+2 | | x+3+-2=10 | | 1/2(2p+1)-(3p+2)=3/4 | | 14m+3n-4m+10n= | | -144=6k | | 6x+3=1x-12 | | 2x-3(x-1)=9 | | 6a+12=2(3a-6)+2a | | 412=4m^2+12 | | 15(15-z)+12z=330 | | 4x+1-6x=5+2x | | 2x+4=5x-1 | | 2x^2-3=15 | | -8(-7x-4)=-360 | | 2x+3(x-1)=32 | | 2-7y+3=4y+17-7y | | -3y^2=-75 | | 7+3(3-2x)=7x+3(3x-3) | | 2-4x=-6x+2 | | 3(4c-1)-6=8c+7 | | 9+b^2=58 | | 4(3x+3)=11x+2 | | C=(b+m)(1+t) | | 6(x-10)=2(x-12) | | (x-1)(x+2)-x(x+3)=(x-2)(x+2)-(x-1)0178 | | -2x-13=7x+23 |

Equations solver categories